(untitled) (Third Sector Social Economic Review, 2025)
Kadro Journal is the publication of an original and important movement. Kadro Journal tried to produce a theory for the Turkish revolution, to turn Kemalism into an ideology and to propose a unique development path for the new Turkey. It has also been claimed that Kadro Journal has an elitist approach. This article is about Kadro Journal and will analyze it within the scope of elitist thought and classical elite theories. The article aims to prove that Kadro Journal has a clearly elitist understanding and that there are reflections of some concepts of classical elite theories in Kadro Journal. The conclusions reached in the article are as follows: Kadro Journal and its authors clearly have an elitist approach. Even the name “Kadro”, which refers to a minority with certain characteristics and distinguished from the larger masses, reflects this elitist approach. However, the elitist approach of Kadro Journal writers; It does not resemble the concept of an elite minority with certain innate superior characteristics adopted by classical elite theorists. It is more similar to the elitist approach that has infiltrated the Marxist understanding and emphasizes the leadership of a revolutionary minority equipped with high consciousness and education for the sake of a certain ideal. In addition, it is possible to find reflections of concepts such as political formula or elite circulation put forward by classical elite theorists in the aims and thoughts of Kadro Journal writers. In the article where data was collected using qualitative research techniques, the information obtained was analyzed in a hermeneutical manner, taking into account the contradictions of the period.